2022
DOI: 10.1007/s40257-022-00675-2
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Manifestations of SARS-CoV-2 Infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused the coronavirus disease 2019 (COVID-19) pandemic, affecting people worldwide. SARS-CoV-2 infection is a multisystem disease with potential for detrimental effects on various systemic organs. It affects people of all ages with varying degrees of disease severity. Patients with SARS-CoV-2 infection commonly present with dry cough, fever, and fatigue. A clinical spectrum of skin findings secondary to SARS-CoV-2 has also been reported. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 49 publications
1
54
0
1
Order By: Relevance
“…During the Cov-19 pandemic, many studies reported a wide spectrum of cutaneous reactions after both SARS-CoV-2 infection and COVID-19 vaccination [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] .…”
Section: Discussionmentioning
confidence: 99%
“…During the Cov-19 pandemic, many studies reported a wide spectrum of cutaneous reactions after both SARS-CoV-2 infection and COVID-19 vaccination [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Some skin manifestations are more common in severe patients, urticarial eruptions are usually an indicator of severe disease. 34 A study in Spain indicates that 19% of COVID‐19 patients had urticarial lesions, which is a bad prognosis, as the mortality rate is 2%. 12 COVID‐19 adults with livedoid lesions tend to need intensive care support.…”
Section: Discussionmentioning
confidence: 99%
“…Our subgroup analysis revealed that I 2 value of studies including severe COVID‐19 patients was 0.0%, indicating that the severity of COVID‐19 was probably the source of heterogeneity in our study. Some skin manifestations are more common in severe patients, urticarial eruptions are usually an indicator of severe disease 34 . A study in Spain indicates that 19% of COVID‐19 patients had urticarial lesions, which is a bad prognosis, as the mortality rate is 2% 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Duration of vesicular eruption has been reported to range between 8 and 10 days [1]. Histology varies according to the lesion ‘age’: ‘early lesions’ feature basal layer vacuolar degeneration, multinucleated and hyperchromatic keratinocytes with dyskeratotic apoptotic cells, and minimal to absent inflammatory infiltrate, while ‘late lesions’ show intraepidermal unilocular vesicles containing multinucleated and ballooned keratinocytes with acantholytic and dyskeratotic cells along with epidermal reticular degeneration [11]. Although diffuse vesicular eruptions, with lesions developing simultaneously on the trunk and spreading distally with possible involvement of the palms and soles have been reported, localized forms with scattered lesions are the most frequent presentations [1,4,12].…”
Section: Covid-19-related Skin Rashesmentioning
confidence: 99%